PENGARUH MUTU PELAYANAN KEPERAWATAN, CITRA RUMAH SAKIT DAN NILAI TERHADAP KEPUASAN PASIEN DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM HAJI SURABAYA - jurnalpps pps; Vinsensius De Paul Wura Lopi; Wasis Budiarto; Bambang Winarto (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
ABSTRACT This study aimed to analyze the effect of Quality of Nursing Service, Hospital Image and Value of Patient Satisfaction in Inpatient Installation of Haji General Hospital Surabaya. This type of research is explanatory research with a quantitative approach. The research instrument used a questionnaire with a Likert scale size of 1 - 5 which was distributed to respondents who were hospitalized in the Inpatient Installation of General Hospital Haji Surabaya as many as 90 people. Based on the results of the hypothesis test t, it shows that the variable quality of nursing services has a significance value of 0,000, the image of the hospital has a significant value of 0.021 and the value has a significance value of 0.020 which means that the significance value is <0.1 so it can be concluded the quality of nursing services hospitals and grades have a partially influence on patient satisfaction. The F test results are known that the significance value is 0,000 <0,1 so that it can be interpreted that the quality of nursing services, hospital image and value simultaneous positive effect on patient satisfaction Keywords: quality of nursing service, hospital image, value, patient satisfaction